2016
DOI: 10.1017/s1751731115002852
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of linseed plus nitrate fed to dairy cows on enteric methane emission and nitrate and nitrite residuals in milk

Abstract: A previous study showed the additive methane (CH 4 )-mitigating effect of nitrate and linseed fed to non-lactating cows. Before practical application, the use of this new strategy in dairy cows requires further investigation in terms of persistency of methanogenesis reduction and absence of residuals in milk products. The objective of this experiment was to study the long-term effect of linseed plus nitrate on enteric CH 4 emission and performance in dairy cows. We also assessed the effect of this feeding stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 20 publications
7
28
1
2
Order By: Relevance
“…As protein is generally the most valuable milk component, an additive that decreases milk protein production may reduce interest in its adoption in practice. Guyader et al (2016) also reported reduced milk protein yield when a combination of nitrate and linseed was fed.…”
Section: Effect On Milk Processing Parametersmentioning
confidence: 95%
See 4 more Smart Citations
“…As protein is generally the most valuable milk component, an additive that decreases milk protein production may reduce interest in its adoption in practice. Guyader et al (2016) also reported reduced milk protein yield when a combination of nitrate and linseed was fed.…”
Section: Effect On Milk Processing Parametersmentioning
confidence: 95%
“…Aschenbach et al (2009) reported that nitrate impaired acetate uptake through the rumen wall in vitro. Nolan et al (2016) suggested this to be a possible explanation for a shift in VFA profile towards acetate that has been reported upon nitrate supplementation, both in vitro and in vivo (Zhou et al, 2012;Guyader et al, , 2016de Raphélis-Soissan et al, 2016a). However, in the study of Aschenbach et al (2009) only acetate uptake was measured, and not uptake of propionate and butyrate.…”
Section: Additivitymentioning
confidence: 96%
See 3 more Smart Citations